Lawrence E. Glendenin papers - Glendenin, Lawrence E. (Lawrence Elgin), 1918-2008.
Correspondence, writings, speeches, subject files, biographical material, newspaper clippings, printed matter, and other papers documenting Glendenin's work on the Manhattan Project, the Bikini Scientific Resurvey, and his career at Argonne National Laboratory. Includes material pertaining to the discovery of Promethium by Glendenin and Jacob A. Marinsky and to the petition to President Harry S. Truman by Oak Ridge National Laboratory scientists which would allow the laboratory to demonstrate the power of the atomic bomb and give Japan the opportunity to surrender. Also includes A General Account of the Development of Methods of Using Atomic Engergy for Military Purposes Under the Auspices of the United States Government, 1941-1945 (1945) written by Henry DeWolf Smyth.
Nuclear chemist and co-discoverer of Promethium, element 61 on the periodic table of elements.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Marinsky, Jacob A. -- 1918-2005.; Smyth, Henry De Wolf, -- 1898-1986.; Truman, Harry S., -- 1884-1972.; Argonne National Laboratory; Bikini Scientific Resurvey; Manhattan Project (U.S.); Oak Ridge National Laboratory; Atomic bomb -- United States; Nuclear weapons -- Research -- United States; Promethium; World War, 1939-1945 -- Japan; World War, 1939-1945 -- United States; Nuclear chemists